Comprehensive Description of Comorbidity for Autism Spectrum Disorder in a General Population - Cawthorpe, David (Perm J, 2016)
CONTEXT: Few published studies of autism spectrum disorder (ASD) and comorbidity are population based. OBJECTIVE: To describe the comorbidity of ASD and disorders listed in the main classes of the International Classification of Diseases, Ninth Revision (ICD-9) in a general population. DESIGN: Direct physician billing data for the city of Calgary, Alberta, Canada, for the treatment of any presenting concern in the Calgary Health Zone (n = 763,449) from 1994 to 2009 were extracted. Diagnosed ICD-9 disorders (independent variable) were grouped into 17 categories using ICD-9 diagnosis codes. ASD (dependent variable) was classified under ICD-9 Code 299. Individuals with and without independent disorder classes were counted by the presence or absence of any ASD. Odds ratios (ORs) and 95% confidence intervals of the association were calculated. MAIN OUTCOME MEASURES: ORs of ASD comorbidities. RESULTS: Annual rates of ASD increased 3.9-fold for males and 1.4-fold for females. Diagnosed disorders ranked by OR in the independent ICD-9 categories indicated that males with ASD had overall higher ORs (> 1.0) in 11 main ICD-9 classes, and females with ASD had higher ORs (> 1.0) in 12 main ICD-9 classes. Males with ASD had lower ORs in 4 main ICD-9 disease classes; females with ASD had lower ORs related only to the main class “complications of pregnancy and childbirth.” Five main ICD-9 classes were not significant for males or females. CONCLUSIONS: Patients with ASD have significant comorbidity of physical disorders. This finding may inform other areas of research and assessment in clinical management.